Moral Rehabilitation of Juvenile Delinquency in Tamalate District, Makassar City (JED (Jurnal Etika Demokrasi), 2021)
Research on the moral rehabilitation of juvenile delinquency in Tamalate sub-district, Makassar city. The purpose of this study (i) to determine the moral rehabilitation process for juvenile delinquency in the Tamalate sub-district, Makassar city. (ii) to determine the effectiveness of juvenile delinquency moral rehabilitation in Tamalate sub-district, Makassar city. The type of this descriptive qualitative research focuses on looking at the social reality of moral rehabilitation for juvenile delinquency. Informants are determined by purposive sampling based on the characteristics of the informants that have been determined. Data collection techniques are observation, interviews, and documentation. The data analysis technique went through several stages, namely data reduction, data presentation and conclusions. The results of this study indicate that, (i) Family, school, and social community have an important role in the moral rehabilitation process for juvenile delinquency in Tamalate sub-district, Makassar city. Various ways are carried out including, more supervision, direction and guidance, and skills. (ii) the effectiveness of moral rehabilitation carried out by the process of supervision, guidance, and skills will be very effective if the three processes run well. Changes in behavior and mindset of adolescents indicate that there is success in rehabilitating, repairing and fostering the behavior of adolescents who deviate. Penelitian tentang rehabilitasi moral kenakalan remaja di kecamatan Tamalate kota Makassar. Tujuan penelitian ini (i) untuk mengetahui proses rehabilitasi moral kenakalan remaja di kecamatan Tamalate kota Makassar. (ii) untuk mengetahui efektifitas rehabilitasi moral kenakalan remaja di kecamatan Tamalate kota Makassar. Jenis penelitian ini kualitatif deskriptif yang berfokus melihat realitas sosial tentang rehabilitasi moral terhadap kenakalan remaja. Informan di tentukan secara purposive sampling berdasarkan karakteristik informan yang telah ditetapkan. Teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Teknik analisis data melalui beberapa tahapan yaitu reduksi data, penyajian data dan kesimpulan. Hasil penelitian ini menunjukkan bahwa, (i) Keluarga, sekolah, dan masyarakat sosial memiliki peran penting dalam proses rehabilitasi moral terhadap kenakalan remaja di kecamatan Tamalate kota Makassar. Berbagai cara yang dilakukan diantaranya yaitu, pengawasan yang lebih, pengarahan dan bimbingan, dan keterampilan. (ii) efektifitas rehabilitasi moral yang dilakukan dengan proses pengawasan, bimbingan, dan keterampilan akan sangat efektif apabila dari ketiga proses tersebut berjalan dengan baik. Perubahan tingkah laku dan pola pikir remaja menunjukkan bahwa terjadi keberhasilan dalam merehabilitasi, memperbaiki dan membina tingkah laku remaja yang melakukan penyimpangan.